Should medical students perform pelvic exams on anaesthetised patients without explicit consent?. (September 2022) - Bell, Chloe; Emmerich, Nathan
There have been many reports of medical students performing pelvic exams on anaesthetised patients without the necessary consent being provided or even sought. These cases have led to an ongoing discussion regarding the need to ensure informed consent has been secured and furthermore, how it might be best obtained. We consider the importance of informed consent, the potential harm to both the patient and medical student risked by the suboptimal consent process, as well as alternatives to teaching pelvic examinations within medical school. The subsequent discussion focuses on whether medical students should perform pelvic examinations on anaesthetised patients without personally ensuring that they have given their explicit consent. Whilst we question the need to conduct pelvic examinations on anaesthetised patients in any circumstance, we argue that medical students should not perform such exams without personally securing the patients informed consent.